Resistance in Murals: Critical Discourse Analysis of the Local Movement in Rejecting the Establishment of a Cement Factory in Rembang - Sarah Rahma Agustin (Department of Communications, Universitas Islam Indonesia, 2022)
This research examines the discourse on rejecting the establishment of the Semen Indonesia factory in Rembang. Taking the murals in Tegaldowo Village, Rembang, as the object study, this study discussed the production of knowledge about the rejection of the factory establishment and power relations in such conflict over the factory establishment. This study applies a visual discourse analysis model developed by Gillian Rose, which includes several essential elements in the text: key themes, justification strategies and their effects, contradictions, positions of the subjects, and location and time of production. This research finds that the movement against the establishment of a cement factory, in addition to going through legal channels, was carried out through cultural media, including by forming discourses that strengthened this rejection. The justification for refusing the establishment is generally based on both traditional and modern ecological discourses. The subjects presented in the text represent the polarization of interests and groups within the local communities, between groups that are pro and contra to the construction of the cement factory, as well as justifying that the cement factory establishment causes such polarization.